2010
DOI: 10.1007/s11426-010-4127-4
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of two novel coordination polymers based on the rigid 1H-1,2,3-triazole-4,5-dicarboxylic acid ligand

Abstract: Two novel three-dimensional (3-D) coordination polymers, [Pb(HTDA)] n (1) and [Co 5 (TDA) 2 (H 2 TDA) 2 (H 2 O) 8 ] n (2) [H 3 TDA = 1H-1,2,3-triazole-4,5-dicarboxylic acid], have been prepared by hydrothermal reactions and characterized by elemental analysis, infrared spectroscopy and single-crystal X-ray diffraction. Compound 1 is constructed from rod-shaped secondary building units (SBUs) and exhibits a 3-D network with (4 10 ·6 5 )(4 10 ·6 3 ·8 2 ) topology. Compound 2 is built up from ligands bridging thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Among various ligands, imidazolate, triazolate, polycarboxylates, and their derivatives have attracted much more attention for constructing a series of metal–organic materials . Much effort has also been focused on syntheses of novel functional materials based on the aromatic organic ligands containing carboxylic and nitrogen donor groups, such as imidazole-4,5-dicarboxylic acid (H 3 IDC), 1,2,3-triazole-4,5-dicarboxylic acid (H 3 tzdc), 1- H -benzimidazole-5-carboxylic acid (H 2 bic), and benzimidazole-5,6-dicarboxylic acid (Hbidc) . These multifunctional ligands easily coordinate with metal ions to form multidimensional complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Among various ligands, imidazolate, triazolate, polycarboxylates, and their derivatives have attracted much more attention for constructing a series of metal–organic materials . Much effort has also been focused on syntheses of novel functional materials based on the aromatic organic ligands containing carboxylic and nitrogen donor groups, such as imidazole-4,5-dicarboxylic acid (H 3 IDC), 1,2,3-triazole-4,5-dicarboxylic acid (H 3 tzdc), 1- H -benzimidazole-5-carboxylic acid (H 2 bic), and benzimidazole-5,6-dicarboxylic acid (Hbidc) . These multifunctional ligands easily coordinate with metal ions to form multidimensional complexes.…”
Section: Introductionmentioning
confidence: 99%
“…In the resulting (3,8)-connected network, the planar tetranuclear Cu II clusters formed via bridging hydroxyl and carboxylate anions act as 8-connected nodes and exhibit antiferromagnetic interactions. Using the connectivity of both carboxylate and triazole groups in 1H-1,2,3-triazole-4,5-dicarboxylic acid, Su and co-workers [10] constructed a 3D (3,4)-connected Co II coordination polymer that displays antiferromagnetic coupling between the Co II ions. More interestingly, Zheng et al [11] synthesized a 1D Co II helical complex with 6-phosphononicotinic acid, in which the metal centers bridged by phosphonate groups show antiferromagnetic interactions.…”
mentioning
confidence: 99%
“…These polymeric complexes exhibit strong solid state emissions at 507-597 nm with different origins, so may be used as green-emitting luminescent materials. As well as d 10 coordination systems, lanthanideorganic frameworks can also display attractive photoluminescence behavior. For example, Zhao et al [12] reported a 2D Eu III coordination polymer that exhibits the characteristic red emission of Eu III in DMF solution.…”
mentioning
confidence: 99%